Nutrition Financing in Senegal - Offosse N., Marie-Jeanne (World Bank, Washington, DC, 2019)
Senegal is known for having one of the most effective and far-reaching nutrition service delivery systems in Africa. Government commitment to improving the nutritional status of the population has increased over time and has been marked, among other things, by the creation in 2001 of the CLM and its Bureau Exécutif National (National Executive Bureau) (BEN); an increase in annual budget allocations to nutrition (from $0.3 million in 2002 to $5.7 million in 2015); and intensificationof community-based nutrition interventions. These commitments are reflected in the improvementof nutrition indicators, notably a 46 percent reduction in under-five stunting from 1992 to 2014.Unfortunately, these improvements have not led to greater visibility of nutrition sensitive interventions in relevant sectors such as agriculture, livestock, education, social protection and health. This shortfall, combined with a recent series of exogenous shocks, has led to recurrent fragmentation of nutrition approaches, paradigms and interventions, resulting in the absence ofa general framework that provides guidance on both nutrition-specific and nutrition-sensitive investments.Meanwhile, progress in reducing stunting has slowed,and low birthweight, iron-deficiency anemia, adolescent undernutrition, and maternal undernutrition have received little attention. These shortcomings threaten the achievements of recent decades. Recognizing this challenge, the government of Senegal joined the Mouvement pour le Renforcement de la Nutrition (Scaling Up Nutrition) SUN Movement in 2011 and adopted the United Nations Approach to Renewed Efforts Against Child Hunger and Undernutrition (REACH) in 2014. These initiatives aim to strengthen institutional capacity and facilitate a multisectoral process to help governments plan, prioritize and more efficiently manage nutrition actions involving multiple stakeholders. With respect to national policy, the government of Senegal has adopted the Politique Nationale de Développement de la Nutrition (National Policy for the Development of Nutrition)(PNDN)2 covering the period 2015 to 2025, which will be operationalized through a multisectoral nutrition strategy, outlined in the Plan Stratégique Multisectoriel de la Nutrition (Multisectoral Nutrition Strategic Plan) (PSNM). These policies aim to expand coverage and improve the quality of nutrition services in sectors whose functional prerogatives affect the prevention and management of malnutrition.